Commentary on "Political engagement in the 2019 UK general election of patients with autism and/or a learning disability detained in a psychiatric hospital". Issue 2 (1st June 2021) - Waltz, Mitzi
Abstract : Purpose: The purpose of this paper is to provide a commentary on the article "Political engagement in the 2019 UK general election of patients with autism and/or a learning disability detained in a psychiatric hospital". Design/methodology/approach: This paper considers the wider issue of political participation by persons with disabilities, especially those whose freedom is restricted. Findings: Access to voting rights remains problematic for many disabled people. It is crucial that this basic form of political participation is ensured, but there is further to go. Originality/value: This paper suggests the need for greater attention to and support for disabled peoples' right to political participation, including people with learning disabilities and autism.